Students' Thinking Process in Solving Mathematical Problems in Build Flat Side Spaces of Material Reviewed from Adversity Quotient - Sari, Indra; Marwan, Marwan; Hajidin, Hajidin (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
Mathematical achievement in problem solving is not yet as expected. This is due to strategies that have not accommodated the situation of students. Â Adversity quontient is the state of the student who needs to get the attention of the teacher so that the learning strategy is expected to be appropriate. This research aims to describe the thinking process of MTs Darul Hikmah students in solving mathematical problems in build side spaces of material reviewed from adversity quotient. This research is in the form of qualitative. The subject selection was done by giving questionnaires to class VIII MTsS Darul Hikmah students and obtained by each one person from each adversity quotient group. The subjects in this study amounted to two students. Data collection is done through tests and interviews, while data analysis uses qualitative data analysis techniques, namely data reduction, data display and conclusions from each adversity quotient group. The results showed that no class VIII students entered the quitters group and the results of the study also showed that class VIII students consisted of climpers and campers. The process of thinking of MTsS Darul Hikmah students based on adversity quotient varied: students in the climbers category namely 3 of 53 students had conceptual thinking processes, while students in the campers category were 27 of 53 students did not have conceptual, semiceptual, or computational thinking processes.